2007
DOI: 10.15560/3.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Amphibia, Anura, Hylodidae, Hylodes charadranaetes: distribution extension and notes on advertisement calls

Abstract: None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Besides, there are isolated occurrence records and ecological observations on some species of frogs (Weber et al 2007, Silva-Soares et al 2008, Klaion et al 2011, MaiaCarneiro et al 2012a, b, 2013, Salles et al 2012), lizards (Goyannes-Araú jo et al 2009, Maia et al 2011, Almeida-Gomes et al 2012, and snakes (Alves et al 2005, Silveira et al 2010). Here, we present the list of amphibian and reptile species based on records obtained during nearly ten years of surveys at REGUA and its surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are isolated occurrence records and ecological observations on some species of frogs (Weber et al 2007, Silva-Soares et al 2008, Klaion et al 2011, MaiaCarneiro et al 2012a, b, 2013, Salles et al 2012), lizards (Goyannes-Araú jo et al 2009, Maia et al 2011, Almeida-Gomes et al 2012, and snakes (Alves et al 2005, Silveira et al 2010). Here, we present the list of amphibian and reptile species based on records obtained during nearly ten years of surveys at REGUA and its surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…40 km for the latter. Meanwhile, Weber et al (2007) reported Hylodes charadranaetes from another locality in the municipality of Cachoeiras de Macacu, extending that species' distribution 43 km eastward.…”
mentioning
confidence: 98%
“…These records extend the known distribution of H. charadranaetes some 60 km eastwards and those of I. octavioi and E. cochranae some 75 km eastwards ( Figure 2), and suggest that those three species may actually be fairly widespread along the Serra do Mar mountain range in the state of Rio de Janeiro. Also, the record of Hylodes charadranaetes represents the lowest altitude at which this species (previously known to occur at altitudes of 700-1400 m; see Weber et al 2007) has been found.…”
mentioning
confidence: 99%